Penerapan Model Pembelajaran Cooperative Learning dalam Membentuk Karakter Siswa pada Mata Pelajaran Fiqh - Ayu Rizkyani; Iwan Hermawan; Nur Aini Farida (Universitas Majalengka, 2023)
Cooperative learning method is a learning method that focuses on the use of small groups of learners to work together in learning to achieve learning goals. Character building is the cultivation of values in students and the renewal of a common life system that respects individual freedom. The purpose of this study is to determine the purpose, process, evaluation, and impact of the cooperative learning model in shaping student character in fiqh class XI at MA Nihayatul Amal Rawamerta. The method used in this research is field research method. The result of this research is that with the application of this cooperative learning model, the teacher can see, and assess the character building in each student through group discussion learning during class learning.